High-strength durable pipe filling master batch and production process thereof
By introducing polysiloxoborane and optimizing the filler composition into the polyolefin material, the problem of poor dispersion of filler in the polyolefin material is solved, and the scratch and impact resistance of the material is significantly improved.
Patent Information
- Application Number
- CN202411841025.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-04-18
AI Technical Summary
The poor dispersion of fillers in existing polyolefin materials leads to the inadequate performance of their properties in polyolefin materials, especially in improving the scratch resistance and impact resistance of polyolefin materials.
A high-strength durable pipe filler is used to filler, which includes filler, polyolefin resin and polysiloxoborane. The dispersion of the filler is enhanced by the introduction of polysiloxoborane, and the impact resistance and tensile strength of the polyolefin sample is improved by optimizing the composition and proportion of the filler.
The mechanical properties and scratch resistance of polyolefin materials are significantly improved, the overall performance of polyolefin samples is improved, and the problem of poor dispersion of fillers in polyolefin materials is solved.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of filling masterbatches, and in particular relates to a high-strength and durable pipe filling masterbatch and a production process thereof. Background Art
[0002] Masterbatch is a concentrate made by loading an extraordinary amount of plastic additives (masterbatch core) into resin. It is made by mixing and kneading various required additives, fillers and a small amount of base resin. The masterbatch is made into various functional plastic products with polyolefins in a certain ratio. As the main variety of filling masterbatch, it is used for filling modification, which is conducive to the uniform dispersion of fillers and more stable molding process, which not only guarantees product quality, but also improves production efficiency, increases the filling amount while meeting the same performance of the product, and reduces costs.
[0003] The main component of the filling masterbatch is filler, such as calcium carbonate, kaolin, talc, wollastonite, etc. The role played by different types of fillers is limited. For example, the fillers on the market now are mainly talc and calcium carbonate. The polyethylene corrugated pipe filled with talc has high rigidity, but low impact strength and is easy to break. The polyethylene corrugated pipe filled with calcium carbonate has high impact resistance and impact strength, but low rigidity and is also easy to deform. Polypropylene pipe is a non-toxic, hygienic, high temperature resistant and recyclable pipe type. It is mainly used in indoor hot and cold water supply systems of buildings and is also widely used in heating systems. However, the surface hardness of general polypropylene pipes is low, and a certain amount of filler needs to be added. On the premise of ensuring that it has good impact resistance, it is also necessary to ensure its scratch resistance. In summary, in order to improve the performance of polyolefin materials, adding fillers as additives is a routine operation, but fillers have poor dispersibility in polyolefin materials, making it difficult to give full play to their performance. Summary of the invention
[0004] The purpose of the present invention is to provide a high-strength and durable pipe filling masterbatch and a production process thereof, so as to improve the performance of polyolefin materials.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A high-strength and durable pipe filling masterbatch comprises filler, polyolefin resin and polysiloxane, wherein the filler accounts for 25-30% of the total mass of the filling masterbatch, and the polysiloxane accounts for 25-30% of the total mass of the filling masterbatch.
[0007] Furthermore, the polysiloxane is obtained by polycondensation reaction of phenylboric acid, a long-chain alkyl silane coupling agent and an epoxy silane coupling agent in a molar ratio of 10:2:2-5.
[0008] Furthermore, the polyolefin resin is at least one of polyethylene resin and polypropylene resin.
[0009] Furthermore, the long-chain alkylsilane coupling agent is one of octyltrimethylhydrogensilane, dodecyltrimethoxysilane and octadecyltrimethoxysilane;
[0010] The epoxy silane coupling agent is γ-glycidyloxypropyltrimethoxysilane.
[0011] Furthermore, the filler includes fibrous filler, flaky filler and powdery filler; the mass ratio of the fibrous filler, flaky filler and powdery filler is 0.3-0.5:1:1.
[0012] Further, the fibrous filler is one of basalt fiber and carbon fiber;
[0013] The flaky filler is one of mica and montmorillonite;
[0014] The powdery filler is one of calcium carbonate and silicon dioxide.
[0015] Furthermore, the particle size of the flaky filler and the powdery filler is 5.5-6.5 μm;
[0016] The fibrous filler has a length of 3-5 mm and a diameter of 10-20 μm.
[0017] Furthermore, the polysiloxane is prepared by the following steps:
[0018] Under the protection of an inert atmosphere, phenylboric acid, a long-chain alkyl silane coupling agent and an epoxy silane coupling agent are dissolved in solvents to obtain a phenylboric acid solution, a long-chain alkyl silane coupling agent solution and an epoxy silane coupling agent solution, respectively; the long-chain alkyl silane coupling agent solution and the epoxy silane coupling agent solution are added dropwise to the phenylboric acid solution, and after the addition, the temperature is raised and stirred to react for 8-10 hours. After the reaction is completed, the solvent is removed to obtain polysiloxane.
[0019] A production process of a high-strength and durable pipe filling masterbatch comprises the following steps:
[0020] The filler, polysiloxane and polyolefin resin were mixed evenly and then added into a twin-screw extruder for extrusion granulation. The temperature ranges of the six heating sections and die of the extruder were: 160±2°C, 170±2°C, 190±2°C, 195±2°C, 205±2°C, 210±2°C, 200±2°C. The screw speed of the extruder was 400-600r / min. After extrusion, it was dried at 80°C and stored.
[0021] Beneficial effects of the present invention:
[0022] The present invention provides a high-strength and durable pipe filling masterbatch, which uses polysiloxane and filler as main raw materials, and synergistically improves the mechanical properties and scratch resistance of the filling masterbatch. The polysiloxane added to the formula of the filling masterbatch improves the dispersibility of the filler, and the introduced polysiloxane can also improve the scratch resistance of a polyolefin sample prepared using the high-strength and durable pipe filling masterbatch as raw material. The introduction of polysiloxane promotes the overall performance improvement of the polyolefin sample.
[0023] In order to further improve the performance of the high-strength and durable pipe filling masterbatch, the scheme of the present invention also optimizes the composition of the filler, which includes fibrous fillers, flaky fillers and powdered fillers. By optimizing the ratio of fibrous fillers, flaky fillers and powdered fillers, the impact resistance and tensile strength of the polyolefin sample are improved.
[0024] In the present invention, the structure of polysiloxane introduces an alkyl long chain (derived from a long-chain alkyl silane coupling agent) and an epoxy structure (epoxy silane coupling agent), wherein the epoxy group can form a chemical bond with an active group such as a hydroxyl group on the surface of the filler to play a role in reaction and volume expansion, and the alkyl long chain can not only improve the dispersibility of the filler, but also improve the interface compatibility between the filler and the polysiloxane and the polyolefin matrix. In addition, the addition of the filler is conducive to improving the hardness of the polyolefin sample, therefore, improving the dispersion of the filler also has a certain improvement on the scratch resistance of the polyolefin sample. DETAILED DESCRIPTION
[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] Preparation Example 1-Preparation Example 4
[0027] Preparation of polysiloxane:
[0028] Referring to the molar ratio of the raw materials shown in Table 1, under nitrogen protection conditions, phenylboric acid, a long-chain alkyl silane coupling agent and an epoxy silane coupling agent are respectively dissolved in 1,2-dichloroethane to obtain a phenylboric acid solution, a long-chain alkyl silane coupling agent solution and an epoxy silane coupling agent solution; the long-chain alkyl silane coupling agent solution and the epoxy silane coupling agent solution are dropwise added to the phenylboric acid solution, and after the addition, the temperature is raised to 80° C., and the reaction is stirred for 8-10 hours. After the reaction is completed, the solvent is removed to obtain polysiloxane.
[0029] Table 1
[0030] project Phenylboronic acid Epoxy silane coupling agent Long chain alkyl silane coupling agent Preparation Example 1 10 2 2 Preparation Example 2 10 2 3 Preparation Example 3 10 2 4 Preparation Example 4 10 2 5
[0031] Preparation Example 5
[0032] Compared with Preparation Example 1, the type of long-chain alkyl silane coupling agent is replaced in this Preparation Example, and dodecyltrimethoxysilane is selected in this Preparation Example.
[0033] Preparation Example 6
[0034] Compared with Preparation Example 1, this Preparation Example replaces the type of long-chain alkyl silane coupling agent, and this Preparation Example selects octadecyltrimethoxysilane.
[0035] Example 1
[0036] This embodiment provides a high-strength and durable pipe filling masterbatch, which includes a filler, a polyolefin resin and the polysiloxane prepared in Preparation Example 1, wherein the filler accounts for 25% of the total mass of the filling masterbatch, and the polysiloxane accounts for 25% of the total mass of the filling masterbatch; the polyolefin resin is a polypropylene resin (copolymer polypropylene (PP): K8703);
[0037] The fillers include fibrous fillers, flaky fillers and powdery fillers; the mass ratio of the fibrous fillers, flaky fillers and powdery fillers is 0.3:1:1. The particle sizes of the flaky fillers and powdery fillers are 5.5-6.5 μm; the length of the fibrous fillers is 3-5 mm and the diameter is 10-20 μm. The fibrous fillers are basalt fibers, the flaky fillers are mica, and the powdery fillers are calcium carbonate.
[0038] A production process of a high-strength and durable pipe filling masterbatch comprises the following steps:
[0039] The filler, polysiloxane and polyolefin resin were added to a high-speed disperser, stirred and dispersed at a speed of 700 r / min for 20 minutes, and added to a twin-screw extruder for extrusion granulation after being mixed evenly. The temperature ranges of the six heating sections and the die of the extruder were: 160±2°C, 170±2°C, 190±2°C, 195±2°C, 205±2°C, 210±2°C, and 200±2°C. The screw speed of the extruder was 400-600 r / min, and after extrusion, it was dried at 80°C and stored.
[0040] Example 2
[0041] This embodiment provides a high-strength and durable pipe filling masterbatch, which includes a filler, a polyolefin resin and the polysiloxane prepared in Preparation Example 1, wherein the filler accounts for 28% of the total mass of the filling masterbatch, and the polysiloxane accounts for 28% of the total mass of the filling masterbatch; the polyolefin resin is a polypropylene resin (copolymer polypropylene (PP): K8703);
[0042] The fillers include fibrous fillers, flaky fillers and powdery fillers; the mass ratio of the fibrous fillers, flaky fillers and powdery fillers is 0.3:1:1. The particle sizes of the flaky fillers and powdery fillers are 5.5-6.5 μm; the length of the fibrous fillers is 3-5 mm and the diameter is 10-20 μm. The fibrous fillers are basalt fibers, the flaky fillers are mica, and the powdery fillers are calcium carbonate.
[0043] A production process of a high-strength and durable pipe filling masterbatch comprises the following steps:
[0044] The filler, polysiloxane and polyolefin resin were added to a high-speed disperser, stirred and dispersed at a speed of 700 r / min for 20 minutes, and added to a twin-screw extruder for extrusion granulation after being mixed evenly. The temperature ranges of the six heating sections and the die of the extruder were: 160±2°C, 170±2°C, 190±2°C, 195±2°C, 205±2°C, 210±2°C, and 200±2°C. The screw speed of the extruder was 400-600 r / min, and after extrusion, it was dried at 80°C and stored.
[0045] Example 3
[0046] This embodiment provides a high-strength and durable pipe filling masterbatch, which includes a filler, a polyolefin resin and the polysiloxane prepared in Preparation Example 1, wherein the filler accounts for 30% of the total mass of the filling masterbatch, and the polysiloxane accounts for 30% of the total mass of the filling masterbatch; the polyolefin resin is a polypropylene resin (copolymer polypropylene (PP): K8703);
[0047] The fillers include fibrous fillers, flaky fillers and powdery fillers; the mass ratio of the fibrous fillers, flaky fillers and powdery fillers is 0.3:1:1. The particle sizes of the flaky fillers and powdery fillers are 5.5-6.5 μm; the length of the fibrous fillers is 3-5 mm and the diameter is 10-20 μm. The fibrous fillers are basalt fibers, the flaky fillers are mica, and the powdery fillers are calcium carbonate.
[0048] A production process of a high-strength and durable pipe filling masterbatch comprises the following steps:
[0049] The filler, polysiloxane and polyolefin resin were added to a high-speed disperser, stirred and dispersed at a speed of 700 r / min for 20 minutes, and added to a twin-screw extruder for extrusion granulation after being mixed evenly. The temperature ranges of the six heating sections and the die of the extruder were: 160±2°C, 170±2°C, 190±2°C, 195±2°C, 205±2°C, 210±2°C, and 200±2°C. The screw speed of the extruder was 400-600 r / min, and after extrusion, it was dried at 80°C and stored.
[0050] Example 4
[0051] Compared with Example 1, the mass ratio of the fibrous filler, the flaky filler and the powdery filler in this example is 0.5:1:1, the fibrous filler is basalt fiber, the flaky filler is mica, the powdery filler is calcium carbonate, and the other raw materials and preparation process remain the same as those in Example 1.
[0052] Example 5
[0053] Compared with Example 1, in this example, the polysiloxane is replaced by the polysiloxane prepared in Preparation Example 2, and the other raw materials and preparation process remain the same as those in Example 1.
[0054] Example 6
[0055] Compared with Example 1, in this example, the polysiloxane is replaced by the polysiloxane prepared in Preparation Example 3, and the other raw materials and preparation process remain the same as those in Example 1.
[0056] Example 7
[0057] Compared with Example 1, in this example, the polysiloxane is replaced by the polysiloxane prepared in Preparation Example 4, and the other raw materials and preparation process remain the same as those in Example 1.
[0058] Example 8
[0059] Compared with Example 1, in this example, the polysiloxane is replaced by the polysiloxane prepared in Preparation Example 5, and the other raw materials and preparation process remain the same as those in Example 1.
[0060] Example 9
[0061] Compared with Example 1, in this example, the polysiloxane is replaced by the polysiloxane prepared in Preparation Example 6, and the other raw materials and preparation process remain the same as those in Example 1.
[0062] Comparative Example 1
[0063] Compared with Example 1, this comparative example does not add fibrous filler to the filler, the mass ratio of mica to calcium carbonate is 1:1, and the other raw materials and preparation process remain the same as those in Example 1.
[0064] Comparative Example 2
[0065] Compared with Example 1, the filler in this comparative example is calcium carbonate, and the other raw materials and preparation process remain the same as those in Example 1.
[0066] Comparative Example 3
[0067] Compared with Example 1, the comparative example is adjusted such that the polysiloxane accounts for 15% of the total mass of the filler masterbatch, and the other raw materials and preparation process remain the same as those in Example 1.
[0068] Prepare the polyolefin samples to be tested, and inject the prepared filling masterbatch into the polyolefin samples to be tested by Example 1 to Example 9, Comparative Example 1 to Comparative Example 2 and the control example, and do not add fillers and polysiloxane in the control example; and perform performance tests:
[0069] The tensile strength is tested according to GB / T1040.1-2018;
[0070] The standard used for the Izod notched impact strength test is ASTM D-256, and the load used is 5.5J;
[0071] The scratch resistance test refers to the standard GMW14688. The cross-hatch instrument is used to scratch the plastic surface. A 0.5mm scratching head is used. Under the pressure of 5N, 20 scratches with a spacing of 4mm and a length of 40mm are scratched on the plastic plate at a speed of 1000mm / min. After scratching in one direction, the plastic plate is rotated 90° and scratched again. Finally. The plastic plate after cross-hatch is compared with the change in gloss before and after scratching using a gloss meter to determine the scratch resistance of the plastic surface. The smaller the change in gloss before and after scratching, the better the scratch resistance of the plastic surface. Expressed by △L, △L=L1 / L2, where L1 is the gloss before scratching and L2 is the gloss after scratching. The results are shown in Table 2:
[0072] Table 2
[0073] sample Tensile strength / MPa Notched impact strength (J / m) △L(L1 / L2) Example 1 27.4 94.5 1.25 Example 2 30.1 96.1 1.22 Example 3 33.2 98.4 1.20 Example 4 27.9 94.8 1.23 Example 5 28.2 95.2 1.21 Example 6 29.2 96.4 1.20 Example 7 29.6 97.2 1.19 Example 8 29.0 96.6 1.20 Example 9 29.5 97.2 1.18 Comparative Example 1 25.6 84.4 1.39 Comparative Example 2 24.1 86.1 1.35 Comparative Example 3 20.5 78.2 1.66 Comparison example 17.4 70.0 2.05
[0074] From the test results, it can be seen that the high-strength and durable pipe filling masterbatch prepared by the present invention has good mechanical properties and scratch resistance. According to the comparison of the test data of Example 1-Example 3, it can be seen that by adjusting the ratio of filler and polysiloxane in the raw material, the mechanical properties of the polyolefin sample will be greatly affected. Increasing the ratio of filler and polysiloxane in the raw material will increase the tensile strength and impact resistance of the polyolefin sample. Combining the data of Comparative Example 3 and the control example, it can be seen that the content of polysiloxane in the polyolefin sample with added filler is too low, which is not conducive to the improvement of mechanical properties. The reason is that in the preparation process of the polyolefin sample, polysiloxane can act as a dispersant, improve the dispersibility of the filler, and improve the overall performance of the polyolefin sample.
[0075] In order to further improve the performance of the high-strength and durable pipe filling masterbatch, the composition of the filler is also optimized in the present invention. The impact resistance and tensile strength of the polyolefin sample are improved by adding fibrous fillers, flaky fillers and powdered fillers. Different fillers play different roles. Since the powdered filler has a granular structure, the addition of the powdered filler will reduce the crystallinity of the polyolefin sample, and the increase in amorphous areas will lead to a decrease in the overall performance of the polyolefin sample. The flaky filler is beneficial to improving the tensile strength and impact resistance of the polyolefin sample, but the performance improvement is limited. The introduction of fibrous fillers in the present invention can reduce the crystallization temperature of the polyolefin sample (the polypropylene used in the embodiment), increase the crystallinity of the polyolefin sample, and then reduce the proportion of amorphous areas, thereby improving the tensile strength and impact resistance of the polyolefin sample.
[0076] In the present invention, the structure of polysiloxane boron introduces an alkyl long chain (derived from a long-chain alkyl silane coupling agent) and an epoxy structure (epoxy silane coupling agent), wherein the epoxy group can form a chemical bond with an active group such as a hydroxyl group on the surface of the filler to play a role in reaction and volume expansion, and the alkyl long chain can not only improve the dispersibility of the filler, but also improve the interface compatibility between the filler and the polysiloxane boron and the polyolefin matrix. In addition, the addition of the filler is conducive to improving the hardness of the polyolefin sample, and the scratch resistance of the polyolefin sample is also improved to a certain extent. According to Comparative Examples 1-2, it can be seen that the improvement effect of the scratch resistance is limited. The addition of polysiloxane boron can not only improve the dispersibility of the filler, but also the scratch resistance data of Examples 5-9 show that the introduction of polysiloxane boron (Si-OBO and alkyl long chain) is also conducive to improving the scratch resistance of the polyolefin sample.
[0077] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0078] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A high-strength and durable pipe filling masterbatch, characterized in that: The invention comprises filler, polyolefin resin and polysiloxane, wherein the filler accounts for 25-30% of the total mass of the filling masterbatch, and the polysiloxane accounts for 25-30% of the total mass of the filling masterbatch.
2. The high-strength and durable pipe filling masterbatch according to claim 1, characterized in that: The polysiloxane is obtained by polycondensation reaction of phenylboric acid, a long-chain alkyl silane coupling agent and an epoxy silane coupling agent in a molar ratio of 10:2:2-5.
3. The high-strength and durable pipe filling masterbatch according to claim 1, characterized in that: The polyolefin resin is at least one of a polyethylene resin and a polypropylene resin.
4. The high-strength and durable pipe filling masterbatch according to claim 2, characterized in that: The long-chain alkylsilane coupling agent is one of octyltrimethylhydrogensilane, dodecyltrimethoxysilane and octadecyltrimethoxysilane; The epoxy silane coupling agent is γ-glycidyloxypropyltrimethoxysilane.
5. The high-strength and durable pipe filling masterbatch according to claim 1, characterized in that: The fillers include fibrous fillers, flake fillers and powdery fillers.
6. The high-strength and durable pipe filling masterbatch according to claim 5, characterized in that: The mass ratio of the fibrous filler, the flaky filler and the powdery filler is 0.3-0.5:1:
1.
7. The high-strength and durable pipe filling masterbatch according to claim 5, characterized in that: The fibrous filler is one of basalt fiber and carbon fiber; The flaky filler is one of mica and montmorillonite; The powdery filler is one of calcium carbonate and silicon dioxide.
8. The high-strength and durable pipe filling masterbatch according to claim 5, characterized in that: The particle size of the flaky filler and the powdery filler is 5.5-6.5 μm; The fibrous filler has a length of 3-5 mm and a diameter of 10-20 μm.
9. The high-strength and durable pipe filling masterbatch according to claim 1, characterized in that: The polysiloxane is prepared by the following steps: Under the protection of an inert atmosphere, phenylboric acid, a long-chain alkyl silane coupling agent and an epoxy silane coupling agent are respectively dissolved in a solvent to obtain a phenylboric acid solution, a long-chain alkyl silane coupling agent solution and an epoxy silane coupling agent solution; the long-chain alkyl silane coupling agent solution and the epoxy silane coupling agent solution are dropwise added to the phenylboric acid solution, and after the addition, the temperature is raised and stirred to react. After the reaction is completed, the solvent is removed to obtain polysiloxane.
10. A process for producing a high-strength and durable pipe filling masterbatch as claimed in any one of claims 1 to 9, characterized in that: The steps include: The filler, polysiloxane and polyolefin resin are mixed evenly and added into a twin-screw extruder for extrusion granulation. After extrusion and drying, a high-strength and durable pipe filling masterbatch is obtained.